KONTINUITETA MOTIVA ZMAJA V MAKEDONSKI KNJIŽEVNOSTI 21. STOLETJA NA PRIMERU ROMANA VLADA UROŠEVIĆA ZMAJEVA NEVESTA - Softić, Una (Philological Studies, 2019)
This article explores the influence of Slavic folk beliefs in dragons on Macedonian literature, from Marko Cepenkov and the Miladinov Brothers to The Dragon’s Bride, a contemporary novel by Vlada Urošević. We examine the parallels between the old and new, tradition and innovation, attitude and interdependence.